Green space in hospital built environment. A literature review about therapeutic gardens in acute care healthcare settings before Covid-19. - Brambilla, Andrea; Del Pio, Matilde; Ravegnani Morosini, Roberto; Capolongo, Stefano (Acta Biomedica Atenei Parmensis, 2023)
Background and aim Hospital facilities are one of the most stressful environments and there is evidence that during Covid-19 having outdoor and green spaces helped medical staff and nurses to decrease the stress and anxiety level. Nevertheless, knowledge about the type of green space is limited. The aim of the study is to systematize the existing scientific literature on the topic in a specific time period. Methods Scopus, Pubmed, and Cochrane library databases have been explored in a systematic way. Following the Prysma diagram 25 studies have been included. Descriptive statistics and content analysis have been performed to highlight green typologies, users and functional area involved, spatial focus, relationship between users and space and vegetation typology. The different topics have been clustered according to Kellert’s biophilic framework. Results Articles reviewed included studies from the 2000 to 2020. The selection led to the analysis of 25 documents; it was significant to understand the major areas of application (pediatrics, ma-ternity, oncology, hospitalization, etc) and forms of green (images, furniture, healing gardens, vegetable gardens, etc). Conclusions The present review highlight the main characteristics of green space in hospital built environment with specific focus on pre-pandemic situation.